Ride, Fly Guy, Ride! - Book 11 - Arnold, Tedd. (New York : Scholastic Inc., 2012)
While riding in the car with Buzz and his father, Fly Guy gets blown out of the window and finds himself riding in a truck, then a boat, a train, an airplane, and maybe even a rocket.
470
Accelerated Reader
Keywords: Flies -- Fiction; Transportation -- Fiction; Automobile travel -- Juvenile fiction; Automobiles -- Juvenile fiction; Flies -- Juvenile fiction; Insects -- Juvenile Fiction; Transportation -- Juvenile fiction; Automobile travel; Automobiles; Flies; Humorous stories; Insects; Picture books for children; Transportation; Flies; Juvenile fiction; Automobile travel; Juvenile fiction; Insects; Juvenile Fiction; Humorous stories; Picture books for children; Juvenile fiction; Automobiles; Juvenile fiction; Transportation; Juvenile fiction; Picture books for children; Flies -- Fiction; Transportation -- Fiction; Humorous fiction; Fiction; Juvenile works; Humorous fiction; Humorous fiction